O-EV002. Auditory event-related potential changes over 6 months following acute organophosphate insecticide poisoning: A follow-up study. Issue 8 (August 2021) - Dassanayake, Tharaka L.; Weerasinghe, Vajira S.; Gawarammana, Indika; Buckley, Nicholas
Abstract : Introduction . Ingestion of organophosphate insecticides (OPIs) is a common method of self-harm and a major clinical problem is Asia. Apart from acute cholinergic effects, OPIs are also claimed to be associated with long-term neurobehavioural deficits. However, neurophysiological evidence for such long-term deficits is scarce in humans. We aimed to assess long-term changes in the pre-attentive (N1) and attentive (P3b) components of auditory event-related potentials (ERPs) following acute OPI self-poisoning. Methods . We recruited 203 patients (147 men) hospitalised following OPI ingestion (OP Group; all had significant red cell cholinesterase inhibition) and 50 patients (23 men) hospitalised with paracetamol overdose (Control Group) as a means of self harm. We recorded their EEG in an auditory oddball task and derived the averaged ERPs. The subjects underwent three testing sessions: on discharge from hospital (around 14 days post-ingestion), 6 weeks and 6 months post-ingestion. We compared the reaction time and ERP indices of the two groups at each time point, adjusting for sex, age, education and psychiatric comorbidities in multiple regression models. Results . After adjusting for covariates, OP Group had significantly slower reaction time than the Control Group on discharge (mean difference [SE] = 65[20] ms, p = 0.001) and at 6 weeks (mean difference [SE] = 45[20] ms, p = 0.024), but not at 6 months. Parietal (PZ) P3b amplitudes were significantly smaller in the OP group on discharge (mean difference [SE] = 2.23[0.84] V, p = 0.009) and at 6 months (mean difference [SE] = 3.34[1.43] V, p = 0.021). P3b latencies or frontal (FZ) N1 component did not show significant intergroup differences. Conclusion . Acute exposure to clinically significant doses of OPIs seem to cause impairment in behavioural and neurophysiological indices of stimulus discrimination, that outlast the cholinergic phase of intoxication. The behavioural impairment seems to disappear over months, but the underlying neurophysiological deficits of attentive processing seem to last even after 6 months post-exposure.